Expanding the phenotype in Adams–Oliver syndrome correlating with the genotype. Issue 1 (25th October 2019) - Dudoignon, Benjamin; Huber, Celine; Michot, Caroline; Di Rocco, Federico; Girard, Muriel; Lyonnet, Stanislas; Rio, Marlène; Rabia, Smail Hadj; Daire, Valérie Cormier; Baujat, Geneviève
Abstract: Rationale: Adams–Oliver syndrome (AOS) is a genetic disorder characterized by the association of aplasia cutis congenita (ACC), terminal transverse limb defect (TTLD), congenital cardiac malformation (CCM), and minor features, such as cutaneous, neurological, and hepatic abnormalities (HAs). The aim of the study is to emphasize phenotype–genotype correlations in AOS. Methods: We studied 29 AOS patients. We recorded retrospectively detailed phenotype data, including clinical examination, biological analyses, and imaging. The molecular analysis was performed through whole exome sequencing (WES). Results: Twenty‐nine patients (100%) presented with ACC, the principal inclusion criteria in the study. Seventeen of twenty‐one (81%) had cutis marmorata telangiectasia congenita, 16/26 (62%) had TTLD, 14/23 (61%) had CCM, 7/20 (35%) had HAs, and 9/27 (33%) had neurological findings. WES was performed in 25 patients. Fourteen of twenty‐five (56%) had alterations in the genes already described in AOS. CCM and HAs are particularly associated with the NOTCH1 genotype. TTLD is present in patients with DOCK6 and EOGT alterations. Neurological findings of variable degree were associated sometimes with DOCK6 and NOTCH1 rarely with EOGT . Conclusion: AOS is characterized by a clinical and molecular variability. It appears that degrees of genotype–phenotype correlations exist for patients with identified pathogenic mutations, underlining the need to undertake a systematic but adjusted multidisciplinary assessment.